Electrolysis treatment study of Sabah bentonite and its applications in petroleum industry - Samsuri, Ariffin (2002)
Based on the result of Geological Survey Department Malaysia investigation, the bentonite resources in Sabah is great amount. In order to reduce the overall cost in oilwell drilling and completion, the development of Sabah bentonite as drilling mud material and oilwell cement additive has been initiated. In addition, Sabah bentonite is categorized as not sodium based bentonite. Appropriate treatment method is sought to replace some of the ions on the unit clay surfaces with sodium ions. One of the methods that purposed is electrolysis treatment method. There are two objectives that can be summarized in this study. The first one was to determine optimum electrolysis treatment. The result obtained after the treatment methods showed improvement in cation exchange capacity (CEC), which is about 27% increment of original CEC value. The higher CEC value indicates the improvement in water absorption capability of bentonite. The second objective was to determine the performance of bentonite as drilling mud material and oilwell cement additive compare with standard bentonite and API (American Petroleum Institute) Specification 13A and 10, respectively.